Substitusi Bungkil Kedelai dengan Ddgs (Distillers Dried Grains and Solubles) terhadap Kandungan Lemak Kasar dan Energi Daging Ikan Nila Merah (Oreochromis niloticus) [Substitution Of Soybean Meal With Ddgs (Distillers Dried Grains And Solubles) Content Of Crude Fat And Energy Meat Red Tilapia (Oreochromis niloticus) ] - Agustono Agustono; Sathiul Inayah; M. Anam Al Arif (Jurnal Ilmiah Perikanan dan Kelautan, 2013)
Abstract Red tilapia (O. niloticus) is a food fish including efforts to increase the commodity into aquaculture production in 2014 amounted to 353%. To support efforts to increase production, so it needed one attempt that the cultivation of tilapia. One effort to reduce the cost of feed needed alternative feed ingredients were good quality. One of the alternatives that are cheap and high nutritional value is DDGS. DDGS is a byproduct from dry milling ethanol industry. Although the by-product of milling corn and the price is cheaper than soybean meal but the nutritional content is similar to soybean meal. From the results of the proximate analysis of DDGS contains 28% protein, 17% fat, 10% crude fiber, 27% and energy BETN 3150 kcal / kg. The results showed that the use of DDGS as a substitute for soybean meal until 80% did not cause significant differences (p> 0.05) on crude fat and energy content of meat red tilapia (O.niloticus).